Pendampingan Kelompok Tani Desa Caraka Jaya dalam Memenuhi Kebutuhan terhadap Pupuk Organik - Nilna Amal; Noordiah Helda; Eko Zulkifli (Universitas Lambung Mangkurat, 2023)
The main objective of community service (PKM) is to empower the community and assist them in solving their problems. A situation analysis of the Caraka Jaya Village farmer groups conducted by the PKM Team of the Civil Engineering Study Program at Lambung Mangkurat University concluded that they need to be assisted in doing something new. The farming community complained about the reduced fertility of their soil compared to before and the presence of new crop pests that were not there previously. They suspect continuously use of chemical fertilizers and pesticides causes this. In order to overcome the situation, other efforts are needed, such as using organic fertilizers and pesticides to reduce dependence on chemical fertilizers. To introduce and encourage them to use organic materials and fertilizers, the PKM Team collaborates with an expert partner of an organic fertilizer consultant to socialize and encourage them to start using organic fertilizers. The socialization was carried out in mid-June 2023 and was attended by more than 20 farmer group members. The socialization went well, and the participants looked enthusiastic, marked by questions about how to apply it and the benefits and weaknesses. At the end of the socialization, it was discovered that some farmers were willing to use the fertilizers and pesticides brought by the PKM Team to their vegetable gardens. At the end of the application, it is hoped that there will be an improvement in vegetable yields and a change in the direction of soil and plant fertility on an ongoing basis, even though it is slow.Keywords: organic fertilizer, empowering, vegetable land, farming groups